This is an example of function composition. Being g and f well defined for the purpose of the composition and x in the domain of f, the composition is:
[tex]g\circ f(x)=g(f(x))[/tex]We can apply this definition to our problem.
Notice that, first, f(x) is calculated and then we used the result (let's called it y) and evaluate it using g (this is g(y))
So, regarding our problem
[tex]\begin{gathered} f(x)=x^2+6x+3 \\ g(x)=2x+8 \\ \Rightarrow \\ f(-5)=(-5)^2+6(-5)+3=25-30+3=-2 \\ \Rightarrow \\ g\circ f(-5)=g(f(-5))=g(-2)=2(-2)+8=-4+8=4 \end{gathered}[/tex]Then
[tex]g\circ f(-5)=4[/tex]